2017
DOI: 10.1128/msphere.00183-17
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii MAF1b Binds the Host Cell MIB Complex To Mediate Mitochondrial Association

Abstract: Parasites interact intimately with their hosts, and the interactions shape both parties. The common human parasite Toxoplasma gondii replicates exclusively in a vacuole in a host cell and alters its host cell’s environment through secreted proteins. One of these secreted proteins, MAF1b, acts to concentrate mitochondria around the parasite’s vacuole, and this relocalization alters the host immune response. Many other intracellular pathogens also recruit host mitochondria, but the identities of the partners tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…94 . Rabbit polyclonal anti-GRA7 95 , anti-MAF1 96 , and anti-SAG1 antibodies were kindly provided by Dr. John C. Boothroyd. Rat anti-HA (3F10) antibodies were obtained from Sigma-Aldrich (Cat#11867431001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…94 . Rabbit polyclonal anti-GRA7 95 , anti-MAF1 96 , and anti-SAG1 antibodies were kindly provided by Dr. John C. Boothroyd. Rat anti-HA (3F10) antibodies were obtained from Sigma-Aldrich (Cat#11867431001).…”
Section: Methodsmentioning
confidence: 99%
“…MAF1 localization was observed in the HFFs infected wild-type, Δ gra45 parasites or Δ gra45 parasites complemented with wild-type or mutant versions of GRA45 . At 4 or 24 h post-infection, the cells were fixed with 4% PFA, permeabilized/blocked with PBS containing 3% (w/v) BSA, 5% (v/v) goat serum and 0.1% Triton X-100 followed by incubation with MAF1 antibodies 96 . To check the PVM localization of GRA23 or export of GRA16 and GRA24, HFFs grown on glass coverslips were infected with wild-type, Δ myr1 , Δ gra45 parasites or Δ gra45 parasites complemented with wild-type or mutant versions of GRA45 transiently expressing GRA23-HA-FLAG, GRA16-HA-FLAG, or GRA16-Ty 50 , GRA24-HA-FLAG or GRA24-Ty 50 for 20–24 h followed by fixation, permeabilization and blocking as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In T. gondii , we and others have identified the parasite locus that is required for host mitochondrial association (HMA), mitochondrial association factor 1B ( MAF1b ) and shown that expression of MAF1b increases cytokine signaling (Pernas et al ., ) during the acute phase of in vivo infections. In infected cell lysates and cells expressing MAF1b ectopically, MAF1b protein interacts with host mitochondrial outer membrane proteins belonging to the MICOS complex, which may be involved in the ability of MAF1b to mediate HMA (Kelly et al ., ). During the acute phase of mouse infections, MAF1b‐expressing parasites outcompete their MAF1b‐null counterparts (Adomako‐Ankomah et al ., ), implying that MAF1b plays an important role in determining infection outcome.…”
Section: Introductionmentioning
confidence: 97%
“…Studies demonstrated that host mitochondrion association is mediated by an interaction between T. gondii MAF1 and the host cell mitochondrial intermembrane space-bridging (MIB) complex (44). In this paper, we identify and characterize a novel E.…”
Section: Introductionmentioning
confidence: 99%